Ecological Impact on Grain Prices Mediated by Rice Production in Pinrang Regency - Sulaiman, Sulaiman; Sudirman, Sudirman; Muhardi, Muhardi (Yayasan Riset dan Pengembangan Intelektual, 2024)
This study aims to analyze the influence of climate change and irrigation intensity on rice production and grain prices both directly and indirectly. The data analysis method used is Two Stage Least Square (2SLS) with 100 farmer samples. The results of the study showed that climate change had a negative and insignificant effect on rice production, while irrigation intensity had a positive and insignificant effect on rice production, other tests showed that climate change had a significant negative effect on grain prices, while irrigation intensity had a significant positive effect on grain prices. In indirect testing, climate change and irrigation intensity have no effect on grain prices through rice production. The government's role is important in strengthening irrigation systems, making climate change mitigation policies to protect farmers from the impact of extreme weather changes, and formulating policies to maintain grain price stability. Farmers are also expected to optimize irrigation management and use the right rice varieties that are resistant to climate change to increase production productivity.